Estrogenic Activity of Mahoni Seed Ethanolic Extract [Swietenia mahogany (L.) Jacq] on Uterus Weight, Bone Density and Mamae Gland Proliferation on Ovariectomized Rats - Hasibuan, Poppy Anjelisa Zaitun; Sitanggang, Rosa Gloria; Angkat, Robbani Syahfitri (Indonesian Journal of Cancer Chemoprevention, 2020)
Menopause is a hypoestrogenic condition due to decreased function of the ovary. During menopause there is no reserved ovum in the ovary, as a result the synthesis of estrogen by the follicles does not take place. Deficiency of estrogen can lead to discomfort and decrease in the women quality of life. Therefore, supplements from natural resources to reduce menopausal symptoms will be needed. The objectives of the study were to determine the effect of mahogany seeds ethanolic extract (MSEE) on the development of uterus, bone density, and mammae gland proliferation on ovariectomized rats. Extract was made by maceration using 96% ethanol as the solvent, then the study of estrogenic effect was carried out on 30 female rats which were divided into 6 groups. Group 1 (normal control), group 2 (positive control) given estradiol dose of 0.18 mg/kg body weight (BW), group 3 (negative control) given Na-CMC 1% and group 4, 5, 6 given MSEE orally for 14 consecutive days with doses of 50, 100, 200 mg/kg BW. Data were analysed using ANOVA then continued with Tukey HSD Post Hoc test to see the differences between the treatments. The results of the study showed that MSEE was able to increase the weight of the uterus, the length of estrus phase in the estrus cycle, bone density and the mammae gland proliferation of rats. The results concluded that MSEE has phytoestrogenic effect on ovariectomized rats.Keywords: phytoestrogen, ovariectomy, uterus weight, bone density, mammae proliferation